Current Trends in IBD—Development of Mucosal-Based Biomarkers and a Novel Minimally Invasive Recoverable Sampling System. (15th November 2021) - Yau, Yunki Y; Wasinger, Valerie C; Hirten, Robert P; Chuang, Emil; Huntsman, Merodean; Stylli, Jack; Shimizu, Jeff; Yajnik, Vijay; Smith, Jeffrey; Lee, Shaoying N; Singh, Sharat; Wahl, Christopher; et al.
Abstract: Despite recent developments in therapy for inflammatory bowel diseases (IBDs), there have been limited advances in diagnostic tools available to aid in disease management. A growing body of evidence suggests that there are important host-microbe interactions at the mucosal interface that modulate the inflammatory response in patients with IBD. Additionally, the importance of mucosal integrity and its disruption appears to be important in the pathophysiology and perpetuation of the disease. The ability to characterize this interface may provide valuable information for both disease monitoring and identification of new treatment targets. Endoscopy remains the primary tool for disease monitoring, and mucosal healing is the primary therapeutic target in IBD treatment. However, establishing mucosal healing requires repetitive endoscopic procedures, and endoscopy is limited by factors such as invasiveness, cost, and risk of adverse events. Moreover, the use of a bowel preparation for colonoscopies alters the mucus layer and thus perturbs evaluation of the host-microbe interaction. Stool sampling may also be inaccurate because it reflects the end state of metabolites and proteins, failing to take into account the degradation or alteration of substrates of interest by bacterial proteases and other enzymes during passage through the colon. A novel sampling capsule, called the Recoverable Sampling System (RSS), is being developed as a complementary tool to colonoscopy. The RSS is intended to be a platform for noninvasive autonomous sampling, preservation, handling, and storage of analytes of interest found in the gastrointestinal fluids. A proprietary preservative contained within the chambers of the capsule has been developed to stabilize DNA and proteins for ex vivo microbiome and metabolomics analyses. Surrogate markers such as SPP24 and GUCA2a have been identified to correlate with gut health, intestinal permeability, and inflammation and could be locally sampled by the RSS. The potential clinical utility of an RSS device is broad and would likely be able to guide therapy by allowing for more frequent disease monitoring, aiding in disease characterization, and facilitating in the identification of novel therapeutic targets. Lay Summary: A new technology is being developed, Recoverable Sampling System (RSS), that may allow sampling without a colonoscopy. This may lead to new biomarkers and even drug targets which may ultimately improve the care of these patients.